Personal branding analysis Jenda Munthe on social media - Rizka Satrio Priyambodo; Neni Yulianita (Jurnal Scientia, 2024)
Everyone can become a content creator, but not everyone can make content creation a profession. Content creator can be defined as someone who makes money by creating content, whether in the form of writing, images, videos, sounds or a combination of this content to be created on online platforms, can be posted on social media, blogs, websites and other online or digital media (Kurniawan & Gabriella, 2020). The name Jenda Munthe or also known as Jenda McLover is a content creator and also a celebrity who actively uses the Tiktok and Instagram applications. Jenda Munthe uses Tiktok & Instagram apart from sharing information and communicating, but also to form Personal Branding. The purpose of this writing is to find out how Jenda Munthe forms Personal Branding and what Jenda Munthe's Personal Branding looks like in the eyes of followers on Instagram.The paradigm in this research is a constructivist paradigm. This writing uses qualitative research methods, with case study research and qualitative descriptive research. Next, use data analysis techniques, literature study and data validity techniques. The theory used in this research is the theory of The Eight Laws of Personal Branding, namely specialization, leadership, personality, difference, visibility, unity, constancy and good name. From the results of the analysis carried out using the eight personal branding concepts from Montoya & Vendehey (2002), this research proves that Jenda Munthe succeeded in building her personal branding well in fulfilling these eight concepts. Jenda Munthe is seen by followers on Instagram as someone who is friendly, kind, easy to get along with, educational and loves her family. Jenda Munthe's personal branding through her Tiktok & Instagram content finally opened up new career opportunities for Jenda Munthe as a content creator who previously worked as a Criminology Journalist. The phenomenon that occurred at Jenda Munthe provides a reality finding that to become a content creator you need the concept of personal branding through content on a media, one of which is the social media Instagram.